Direct Hybridization Fuel Cell – Ultracapacitors1. Issue 3 (3rd June 2014) - Morin, B.; Van Laethem, D.; Turpin, C.; Rallières, O.; Astier, S.; Jaafar, A.; Verdu, O.; Plantevin, M.; Chaudron, V.; Steiner, Nadia; Hissel, Daniel; Bultel, Yann
Abstract It is now well recognized that highly dynamic power demands accelerate the ageing of a fuel cell. A solution is to hybridize it with an electrochemical storage device (ultracapacitors, Li‐ion battery...). Whatever the technique implemented to manage energy, the hybridization principle forces the storage device to take in charge the rapid power changes to protect the fuel cell. Several electrical architectures are possible to interconnect the fuel cell and the storage device: indirect hybridization via power converters, or direct hybridization without power converters. The work here focuses on direct hybridization between a fuel cell and ultracapacitors. Classically, this kind of connection concerns the hybridization of a fuel cell stack with an ultracapacitors' pack. The authors here investigate another rather original option by implementing this hybridization at the scale of each cell of a fuel cell stack. In this approach, each elementary ultracapacitor can be connected either to one cell or to two cells. Before applying the concept to a real fuel cell stack (the final objective), the authors studied the concepts with single cells. This paper is going to present the intensive experimental works achieved to apprehend the principles. Static and dynamics properties of such hybridization are analyzed and modeled.